Composição florística e banco de sementes das comunidades de macrófitas aquáticas em afloramentos hídricos no semiárido. - Deus, Maria do Socorro Meireles de (2016)
The macrophytes plants are critical to the ecological functions of aquatic environments, giving sustainability to a large number of organism. The objectives were: (i) to evaluate the composition and distribution of macrophytes in water outcrops in the northeastern semi-arid region and (ii) determine whether the sediment seed bank is responsible for the restoration of aquatic vegetation of these places. Samples were collected in environments lotic (N = 2) and lentic (N = 7) in the year 2014. In each of the different environments were three samples at different points. And each point was used a square of 1m x 1m positioned each 2m along a transect and species located inside the square were recorded. Soil samples were collected for subsequent germination of the seed bank. The following abiotic water parameters were measured in situ at each point: transparency values of secchi disc, conductivity, nitrogen and phosphorus. The following statistical analyzes were performed for both data sampled in situ and the seed bank. For species richness, species accumulation curves were used. The variation in species composition between sampling sites was measured using a metric multidimensional scaling (MDS) and variation in species composition between sampling sites, according to environmental variables, by Canonical Analysis Coordinates Main. Was performed linear regressions with the species richness as the response variable and environmental variables as a predictor for the sampled in situ data. They recorded 49 species belonging to 22 families and 39 genera. The depth, radiation percentage in the sediment, environment type and the array index, explained species richness. The type of environment sampled, characterization array index and conductivity mainly explained the change in species composition. The richness and species composition vary between lentic and lotic environments, physical and chemical characteristics are important to determine the richness and composition of aquatic flora of these environments. The seed bank does not fully explain the composition of macrophytes meetings of the studied environments.